Permodelan dan Bentuk Hukum Pokok-Pokok Haluan Negara sebagai Payung Hukum Pelaksanaan Pembangunan Berkesinambungan dalam Rangka Menghadapi Revolusi Industri 5.0 dan Indonesia Emas - Eka Martiana Wulansari (Penerbit Goodwood, 2023)
Purpose: This article discusses the legal form of the principles of state policy as a legal umbrella for the implementation of sustainable development in the context of facing the 5.0 industrial revolution and golden Indonesia. Methodology The discussion in this article is that the main forms of state policy as a legal umbrella for the implementation of sustainable development in the context of facing the 5.0 industrial revolution and golden Indonesia, this is necessary considering that the National Medium Term Development Plan (RPJM) has weaknesses such as the forming actors who do not representative, implementing actors who are not related to the essence of implementing people's sovereignty, that by changing the formulation of Article 1 paragraph (2) of the 1945 Constitution of the Republic of Indonesia, the mechanism of community control over the implementation of the National Long-Term Development Plan (RPJPN) and/or RPJMN is ineffective. Results: So that a role and legal instruments are needed in the form of the main points of state policy as a legal umbrella for the implementation of development in the form of re-establishing the Outline of State Policy (GBHN) and as a guiding indicator in planning and supervising the government's commitment, namely the President and Vice President as executive bodies.